Visit of Prime Minister Dr. Manmohan Singh to South Africa, September 30 - October 03, 2006 - Manmohan Singh 1932-; India. Ministry of External Affairs. Public Diplomacy Division (New Delhi Public Diplomacy Division, Ministry of External Affairs, Government of India, 2006)
Transcript of speeches delivered during his South Africa visit.
"December 2006."
Keywords: Manmohan Singh -- 1932- -- Speeches -- Selections; Manmohan Singh -- 1932- -- Travel -- South Africa; Visits of state -- South Africa; India -- Foreign relations -- South Africa; South Africa -- Foreign relations -- India